Silver nanoparticles: A boon in clinical medicine - Aashritha Shenava; S Mahalinga Sharma; Veena Shetty; Shilpa Shenoy (Wolters Kluwer Medknow Publications, 2015)
Silver nanoparticles (AgNP) have unique properties which help in molecular diagnostics, in therapies, as well as in devices that are used in several medical procedures. AgNP are nanoparticles of silver which are in the range of 1 and 100 nm in size. The major methods used for AgNP synthesis are the physical and chemical methods. The major applications of AgNP in the medical field include diagnostic applications and therapeutic applications. In most of the therapeutic applications, it is the antimicrobial property that is being majorly explored though the anti-viral property has its fair share of applications. This review provides a comprehensive view on the synthesis and applications of nanoparticles in the medical field. The focus is on exploring their various prospective applications besides trying to understand the current scenario.